2004
DOI: 10.1097/00043426-200407000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Children With B-Cell Non-Hodgkinʼs Lymphoma in Developing Countries: The Experience of a Single Center in Brazil

Abstract: This strategy was very effective for treating B-NHL in a developing country. The results were comparable to those of the BFM 90 study and other contemporary groups and represented an increase in the cure rates in childhood B-NHL in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…The present study describes the epidemiological and clinical characteristics of 142 Egyptian pediatric NHL patients admitted to two Pediatric Oncology Units. Patients aged <10 years consituted >88.5% of our study sample and there was a trend toward a decrease of the relative incidence with increasing age, with 88.5 and 11.5% for the age groups of 0-10 and >10 years, respectively, which was consistent with previously reported findings (16)(17)(18). Sandlund et al (1) and Manipadam et al (19) reported that the incidence of NHL increases uniformly with age and is rarely diagnosed before 2 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study describes the epidemiological and clinical characteristics of 142 Egyptian pediatric NHL patients admitted to two Pediatric Oncology Units. Patients aged <10 years consituted >88.5% of our study sample and there was a trend toward a decrease of the relative incidence with increasing age, with 88.5 and 11.5% for the age groups of 0-10 and >10 years, respectively, which was consistent with previously reported findings (16)(17)(18). Sandlund et al (1) and Manipadam et al (19) reported that the incidence of NHL increases uniformly with age and is rarely diagnosed before 2 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…The possibility of an infectious etiology, principally associated with Epstein-Barr virus (EBV) (12), being involved in the pathogenesis of NHL may be a partial explanation of the emergence of this disease in younger patients in our region, as populations of lower socioeconomic status are presumably exposed to infectious agents earlier in life. The incidence of childhood NHL was generally higher in male (63.4%) compared to female (36.6%) patients and this male predominance of childhood lymphoma mirrors the reported general pattern of male predominance exhibited by lymphoid malignancies, but not by all types of cancer (16,18). Although the majority of lymphomas in adults are of low or intermediate grade, >90% of childhood NHLs are of high grade and may be classified into one of four main categories (20).…”
Section: Discussionsupporting
confidence: 58%
“…In general, BL/L has been associated with a particular good prognosis when treated with intensive chemotherapy regimens. In Brazil, the event-free survival rate for Burkitt lymphoma patients treated with BFM 90 is about 80%, being 100% for stage I/II and about 75% for stage III/IV patients [14], which is comparable to the results of the BFM 90 study and other current BL/L protocols. Besides classical risk factors, such as advanced stage, high LDH, and combined BM and CNS disease, it has been described that secondary abnormalities, such as 1q, 7q, 13q and 12q could influence the prognosis of the patient.…”
Section: Discussionsupporting
confidence: 69%
“…3 In our study we observed that NHL affects younger children than those described in foreign literature and this fact is compatible with other reports that have described other Brazilian experiences. 6,7,15,16 The possibility of infectious etiology, principally related to the Epstein-Barr virus, 4 being involved in the pathogenesis of Burkitt lymphomas may be a partial explanation for the emergence of this disease in younger patients in our region, since it is believed that populations in less privileged socioeconomic situations are exposed to infectious agents earlier.…”
Section: Discussionmentioning
confidence: 99%